Studi Tentang Pengaruh Kepemimpinan Transformasional, Work Life Balance Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Industri Food & Beverage Di Kota Malang (Studi Pada Karyawan F&B Sudimoro Kota Malang) - Jalil, Irfan Abdul; Pardiman, Pardiman; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze and describe the effect of Transformational Leadership, Work Life Balance, and Work Motivation on Employee Performance in the Food and Beverage Industry in Malang City (study on f&b sudimoro employees in Malang City) The population in this study were F&B sudimoro employees in Malang City. Determination of the number of samples using the Mahoeltra formula and obtained results as many as 70 respondents. Data collection is done using a questionnaire. To solve the problem in this study using the help of SPSS with the analysis method used in this study is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, t test, coefficient of determination test (R2). The results of the research Transformational Leadership, Work Life Balance, and Work Motivation have a significant effect on Employee Performance. Keywords: Employee performance, Transformational Leadership, Work Life Balance and Work Motivation